Chapter 9.1 Overview By a sequence, we mean an arrangement of numbers in a definite order according to some rule. We denote the terms of a sequence by a1, a2, a3, ... , etc., the subscript denotes the position of the term. In view of the above a sequence in the set X can be regarded as a mapping or a function f : N → X defined by f (n) = tn ∀ n ∈ N. Domain of f is a set of natural numbers or some subset of it denoting the position of term. If its range denoting the value of terms is a subset of R real numbers then it is called a real sequence. A sequence is either finite or infinite depending upon the number of terms in a sequence. We should not expect that its terms will be necessarily given by a specific formula. However, we expect a theoretical scheme or rule for generating the terms. Let a1, a2, a3, ... , be the sequence, then, the expression a1 + a2 + a3 + ... is called the series associated with given sequence. The series is finite or infinite according as the given sequence is finite or infinite. Remark When the series is used, it refers to the indicated sum not to the sum itself. Sequence following certain patterns are more often called progressions. In progressions, we note that each term except the first progresses in a definite manner. 9.1.1 Arithmetic progression (A.P.) is a sequence in which each term except the first is obtained by adding a fixed number (positive or negative) to the preceding term. Thus any sequence a1, a2, a3 ... an, ... is called an arithmetic progression if an + 1= an + d, n ∈ N, where d is called the common difference of the A.P., usually we denote the first term of an A.P by a and the last term by l The general term or the nth term of the A.P. is given by an = a + (n – 1) d The nth term from the last is given by an = l – (n – 1) d The sum Snof the first n terms of an A.P. is given by n n+Sn = 2 [2an ( −1) d]= 2(al + ) , where l= a+ (n– 1) d is the last terms of the A.P., and the general term is given by a= S – S nnn– 1 The arithmetic mean for any npositive numbers a, a, a, ... ais given by123naa + ... + a+ nA.M. = 1 2 n If a, A and b are in A.P., then A is called the arithmetic mean of numbers aand band ab+ i.e., A = 2 If the terms of an A.P. are increased, decreased, multiplied or divided by the same constant, they still remain in A.P. If a1, a2, a3 ... are in A.P. with common difference d, then (i) a1 ± k, a2 ± k, a3 ± k, ... are also in A.P with common difference d. (ii) ak, ak, ak, ... are also in A.P with common difference dk(k≠ 0).1 23 aa a123 dand , , ... are also in A.P. with common difference (k≠ 0).kkkkIf a, a, a... and b, b, b ... are two A.P., then 123123(i) a± b1, a± b2, a± b, ... are also in A.P 123 3aa a123 ,,(ii) ab1, ab2, ab, ... and bb b, ... are not in A.P.1 2 3 3 12 3 If a1, a2, a3 ... and an are in A.Ps, then (i) a+ a= a2 + a = a3 + a = ...1 nn– 1n– 2a + ark− rk(ii) ar = 2 +∀ k, 0 ≤ k≤ n– r (iii) If nth term of any sequence is linear expression in n, then the sequence is an A.P. (iv) If sum of nterms of any sequence is a quadratic expression in n, then sequence is an A.P. 9.1.2 A Geometric progression (G.P.) is a sequence in which each term except the first is obtained by multiplying the previous term by a non-zero constant called the common ratio. Let us consider a G.P. with first non-zero term a and common ratio r, i.e., a, ar, ar2, ... , arn – 1, ... n–1arHere, common ratio r = n–2ar The general term or nth term of G.P. is given by an = arn – 1. Last term l of a G.P. is same as the nth term and is given by l = arn – 1. l and the nth term from the last is given by an = n− 1r The sum Sn of the first n terms is given by ( n − 1) S = ar , if r ≠ 1 nr −1 Sn = na if r = 1 If a, G and b are in G.P., then G is called the geometric mean of the numbers a and b and is given by G = ab (i) If the terms of a G.P. are multiplied or divided by the same non-zero constant (k≠ 0), they still remain in G.P. aa a1 2 3If a1, a2, a, ... , are in G.P., then ak, ak, ak, ... and , , , ...3 123 kkk are also in G.P. with same common ratio, in particularly if a1, a2, a3, ... are in G.P., then 111 , ,aa a , ... are also in G.P. 1 23 (ii) If a1, a2, a3, ... and b1, b2, b3, ... are two G.P.s, then a1 b1, a2 b2, a3 b3, ... and aa a1 23 , , b , ... are also in G.P. bb1 2 3 a aa1 23(iii) If a1, a2, a3, ... are in A.P. (ai > 0 ∀ i), then x , x , x , ..., are in G.P. ( ∀ x > 0) (iv) If a1, a2, a3, ..., a are in G.P., then a = a= a = ...n1 an2 an– 1 3 an– 29.1.3 Important results on the sum of special sequences (i) Sum of the first nnatural numbers: ( +1) nn∑123... nn=+++ += 2 (ii) Sum of the squares of first nnatural numbers. 2222 2 nn( +1) (2 n+1) ∑n=+ +++ 1 2 3 ... n= 6 (iii) Sum of cubes of first nnatural numbers: nn3333 3 ⎡( +1) ⎤2 n=+ +++ 12 3... n=∑ ⎢⎥⎣ 2 ⎦ 9.2 Solved Examples Short Answer Type Example 1 The first term of an A.P. is a, the second term is band the last term is c. (bc aca 2 )( ++− )Show that the sum of the A.P. is . 2(ba)− Solution Let dbe the common diffrence and n be the number of terms of the A.P. Since the first term is aand the second term is b Therefore, d= b– a Also, the last term is c, so c= a+ (n– 1) (b– a) (since d= b– a) ca− ⇒ n– 1 = ba− ca baca bc−+− +− 2− a ⇒ n =1+ = = ba−ba− ba − n(bc a +−2) +)Therefore, S n =(al+) = (ac 2 2(ba−) Example 2 The pth term of an A.P. is aand qth term is b. Prove that the sum of its (p+ q) terms is p+q ab ⎤⎡ab −− ⎥⎢++ .2 ⎣ pq⎦Solution Let A be the first term and D be the common difference of the A.P. It is given that tp = a⇒ A + (p– 1) D = a ... (1) tq =b ⇒ A + (q– 1) D = b ... (2) Subtracting (2) from (1), we get (p– 1 – q+ 1) D = a– b ab− ⇒ D = ... (3)p−q Adding (1) and (2), we get 2A + (p+ q– 2) D = a+ b ⇒ 2A + (p+ q– 1) D = a+ b+ D ab− ⇒ 2A + (p+ q– 1) D = a+ b+ .. (4)p−q p+qNow S = [2A + (p+ q– 1) D]p+ q2 p+q−⎡ab ab ⎤ ⎢++ 2 ⎣ p−q⎦⎥= [(using ... (3) and (4)] Example 3 If there are (2n + 1) terms in an A.P., then prove that the ratio of the sum of odd terms and the sum of even terms is (n+ 1) : n Solution Let abe the first term and d the common difference of the A.P. Also let S1 be the sum of odd terms of A.P. having (2n + 1) terms. Then S1 = a1 + a3 + a5 + ... + a2n+ 1 n+1 (aa+)S1 = 1 +2n12 n+1 S1 = 2 [aa(2 +− 1 1) d]++ n =(n + 1) (a + nd) Similarly, if S2 denotes the sum of even terms, then S = n [2a + 2nd] = n (a + nd)22 S(n +1) ( a + nd ) n +1 Hence 1 = = S2 na( + nd ) n Example 4 At the end of each year the value of a certain machine has depreciated by 20% of its value at the beginning of that year. If its initial value was Rs 1250, find the value at the end of 5 years. Solution After each year the value of the machine is 80% of its value the previous year so at the end of 5 years the machine will depreciate as many times as 5. Hence, we have to find the 6th term of the G.P. whose first term a1 is 1250 and common ratio r is .8. Hence, value at the end 5 years = t6 = a1 r5 = 1250 (.8)5 = 409.6 Example 5 Find the sum of first 24 terms of the A.P. a1, a2, a3, ... if it is known that a + a + a + a + a + a = 225.1510152024Solution We know that in an A.P., the sum of the terms equidistant from the beginning and end is always the same and is equal to the sum of first and last term. Therefore d = b – a i.e., a1 + a24 = a5 + a20 = a10 + a15 It is given that (a + a) + (a + a) + (a + a) = 2251245201015⇒ (a + a) + (a + a) + (a + a) =225 124 124124⇒ 3 (a1 + a24) = 225 ⇒ a1 + a24 =75 n [alWe know that Sn = + ], where a is the first term and l is the last term of an A.P.2 24 Thus, = [a1 + a24] = 12 × 75 = 900S242Example 6 The product of three numbers in A.P. is 224, and the largest number is 7 times the smallest. Find the numbers. Solution Let the three numbers in A.P. be a – d, a, a + d (d > 0) SEQUENCE AND SERIES 153 Now (a – d) a (a + d) = 224 ⇒ a (a2 – d2) = 224 ... (1) Now, since the largest number is 7 times the smallest, i.e., a + d = 7 (a – d) 3aTherefore, d = 4 Substituting this value of d in (1), we get ⎛ 9a 2 ⎞ aa 2 ⎟ 224⎜− = ⎝ 16 ⎠a =8 3a 3 =and d = =×86 44 Hence, the three numbers are 2, 8, 14. Example 7 Show that (x2 + xy + y2), (z2 + xz + x2) and (y2 + yz + z2) are consecutive terms of an A.P., if x, y and z are in A.P. Solution The terms (x2 + xy + y2), (z2 + xz + x2) and (y2 + yz + z2) will be in A.P. if (z2 + xz + x2) – (x2 + xy + y2) = (y2 + yz + z2) – (z2 + xz + x2) y2i.e., z2 + xz – xy – = y2 + yz – xz – x2 i.e., x2 + z2+ 2xz – y2 = y2 + yz + xy i.e., (x + z)2 – y2 = y (x + y + z) i.e., x + z – y = y i.e., x + z =2y which is true, since x, y, z are in A.P. Hence x2 + xy + y2, z2 + xz + x2, y2 + yz + z2 are in A.P. Example 8 If a, b, c, d are in G.P., prove that a2 – b2, b2 – c2, c2 – d2 are also in G.P. Solution Let r be the common ratio of the given G.P. Then bc d = = =r ab c ⇒ b = ar, c = br = ar2, d = cr = ar3 Now, a2 – b2 = a2 – a2r2 = a2 (1 – r2) b2 – c2 = a2 r2 – a2r4 = a2 r2 (1 – r2) and c2 – d2 = a2 r4 – a2r6 = a2 r4 (1 – r2) 22 22b − cc − d 2Therefore, = = r22 22a −bb − c Hence, a2 – b2, b2 – c2, c2 – d2 are in G.P. Long Answer Type Example 9 If the sum of m terms of an A.P. is equal to the sum of either the next n terms or the next p terms, then prove that ⎛ 11 ⎞⎛ 11 ⎞ =(mp) −−+(m + n) ⎜⎟ ⎜⎟⎝ mp ⎠⎝ mn ⎠ Solution Let the A.P. be a, a + d, a + 2d, ... . We are given a + a + ... + a = a + a + ... + a ... (1)12mm+1m+2m+n Adding a1 + a2 + ... + am on both sides of (1), we get 2 [a1 + a2 + ... + am] = a1 + a2 + ... + am + am+1 + ... + am+n 2 S m = Sm+n mm+ n Therefore, 2 {+( −1) d}= {2 + (m+n 1) 2am a − d}22 Putting 2a + (m – 1) d = x in the above equation, we get mn+mx = (x + nd)2 (2m – m – n) x =(m + n) nd ⇒ (m – n) x =(m + n) nd ... (2) Similarly, ifa + a + ... + a = a + a + ... + a12mm + 1m + 2m + p Adding a + a + ... + a on both sides12mwe get, 2(a + a + ... + a ) = a + a + ... + a + ... + a12m12m + 1m + p or, 2 S =Smm + p ⎡m ⎤+⇒ 2 {2 a + (m− d⎢ 1) } ⎥= mp {2a + (m + p – 1)d} which gives⎣ 2 ⎦ 2 i.e., (m – p) x =(m + p)pd ... (3) Dividing (2) by (3), we get ( − ) x (mn)mn+ nd = (mp) x ( + )− mppd ⇒ (m– n) (m+ p) p=(m– p) (m+ n) n Dividing both sides by mnp, we get ⎛ 11 ⎞⎛ 11 ⎞ (m+ p) ⎜− ⎟ =(m+ n) ⎜− ⎟⎝ nm⎠⎝ pm⎠ ⎛ 11 ⎞⎛ 11 ⎞− −= (m+ n) ⎜⎟ =(m+ p) ⎜⎟⎝ mp⎠⎝ mn⎠ Example 10 If a1, a, ..., a are in A.P. with common difference d(where d≠ 0);2nthen the sum of the series sin d(cosec a1 cosec a2 + cosec a2 cosec a3 + ...+ cosec an–1 cosec an) is equal to cot a1 – cot an Solution We have sin d(cosec a1 cosec a2 + cosec a2 cosec a3 + ...+ cosec an–1 cosec an) ⎡ 11 1 ⎤sin d ++...+= ⎢ ⎥sin asin a sin asin a sin a sin a⎣ 12 23 n−1 n⎦ − ) sin ( aa ) sin( aa )sin ( aa − −2 1 32 nn−1 = ++...+ sin asin a sin asin a sin a sin a12 23 n−1 n sin acos a− cos asin a) sin acos a− cos asin a) sin acos a −cos asin a )2 121 3232 nn−1 nn−1+ +... += sin a1sin a2 sin asin a3 sin an− sin a2 1 n = (cot a– cot a) + (cot a– cot a) + ... + (cot a – cot a)1223n–1n= cot a– cot a1n Example 11 (i) If a, b, c, d are four distinct positive quantities in A.P., then show that bc> ad (ii) If a, b, c, dare four distinct positive quantities in G.P., then show that a+ d> b+ c Solution (i) Since a, b, c, d are in A.P., then A.M. > G.M., for the first three terms. ⎛ ac+⎞Here =bTherefore, b > ⎜⎟ac ⎝ 2 ⎠ Squaring, we get b2 > ac ... (1) Similarly, for the last three terms AM > GM ⎛ bd+⎞Here = cc > bd ⎜⎟⎝ 2 ⎠ c2 > bd ... (2) Multiplying (1) and (2), we get b2c2 > (ac) (bd) ⇒ bc > ad (ii) Since a, b, c, d are in G.P. again A.M. > G.M. for the first three terms ac+ > b (since ac =b)2 ⇒ a + c > 2b ... (3) Similarly, for the last three terms bd+since bd =c)> c (2 ⇒ b + d > 2c ... (4) Adding (3) and (4), we get (a + c) + (b + d) > 2b + 2c a + d > b + c Eample 12 If a, b, c are three consecutive terms of an A.P. and x, y, z are three consecutive terms of a G.P. Then prove that xb – c a. yc – . za – b = 1 Solution We have a, b, c as three consecutive terms of A.P. Then b – a = c – b = d (say) c – a =2d a – b =– d b– cc– aa – d2d– d– b=Now x . y . z x . y . z 2d − d= x – d ( xz). z (since y=( xz)) as x, y, z are G.P.) – ddd– d= x . x. z. z – d+ dd– d= x . z= x° z° = 1 n Example 13 Find the natural number afor which ∑fa k ( + ) = 16(2n– 1), where k=1 the function fsatisfies f(x+ y) = f(x) . f(y) for all natural numbers x, yand further f(1) = 2. Solution Given that f(x+ y) = f(x) . f(y) and f(1) = 2 Therefore, f(2) = f(1 + 1) = f(1) . f(1) = 22 f(3) = f(1 + 2) = f(1) . f(2) = 23 f(4) = f(1 + 3) = f(1) . f(3) = 24 and so on. Continuing the process, we obtain f(k) = 2kand f(a) = 2a nn fa k (). () Hence ∑( + ) = ∑ fa fk k=1 k=1 n fk= f(a) ∑ () k=1 =2a(21 + 22 + 23 + ... + 2n) n⎧ 2. 2 −1 ⎫⎪( )⎪a a+1 n2 ⎨ ⎬= 2 (2 −1) = ... (1)21−⎪⎪⎩⎭ n fa k But, we are given ∑ ( + )= 16 (2n– 1)k=1 2a+ 1 (2n – 1) = 16 (2n– 1) ⇒ 2a+1 =24 ⇒ a+ 1 = 4 ⇒ a=3 Objective Type Questions Choose the correct answer out of the four given options in Examples 14 to 23 (M.C.Q.). Example 14 A sequence may be defined as a (A) relation, whose range ⊆ N (natural numbers) (B) function whose range ⊆ N (C) function whose domain ⊆ N (D) progression having real values Solution (C) is the correct answer. A sequence is a function f : N → X having domain ⊆ N Example 15 If x, y, z are positive integers then value of expression (x + y) (y + z) (z + x) is (A) = 8xyz (B) > 8xyz (C) < 8xyz (D) = 4xyz Solution (B) is the correct answer, since xy+ yz+ +A.M. > G.M., 2 > xy, >yz and zx > zx 2 2 Multiplying the three inequalities, we get xyyzyz+ ++ .. > ( )()() zx xyyz 2 22 or, (x + y) (y + z) (z + x) > 8 xyz Example 16 In a G.P. of positive terms, if any term is equal to the sum of the next two terms. Then the common ratio of the G.P. is (A) sin 18° (B) 2 cos18° (C) cos 18° (D) 2 sin 18° Solution (D) is the correct answer, since t = t + t nn+1n+2 ⇒ arn–1 = arn + arn+1 ⇒ 1 = r + r2 15−± r = , since r > 0 2 51−Therefore, r = 2 = 2 sin 18° 4 Example 17 In an A.P. the pth term is qand the (p+ q)th term is 0. Then the qth term is (A) – p (B p (C) p+ q (D) p– q Solution (B) is the correct answer Let a, d be the first term and common difference respectively. Therefore, Tp = a+ (p– 1) d= qand ... (1) Tp+ q = a+ (p+ q– 1) d= 0 ... (2) Subtracting (1), from (2) we get qd= – q Substituting in (1) we get a= q– (p– 1) (–1) = q+ p– 1 Now T = a+ (q– 1) d= q+ p– 1 + (q– 1) (–1)q= q+ p– 1 – q+ 1 = p Example 18 Let S be the sum, P be the product and R be the sum of the reciprocals of 3 terms of a G.P. Then P2 R3 : S3 is equal to (A) 1 : 1 (B) (common ratio)n: 1 (C) (first term)2 : (common ratio)2 (D) none of these Solution (A) is the correct answer a Let us take a G.P. with three terms ,, r. Then aar ar (2 r 1) a ++S = ++aar= rr r 111 ⎛r2 r 1++⎞ P = a3, R = ++=⎜ ⎟ aa ar a⎝ r ⎠ ⎛23 61 r ++1⎞ a⋅⎜ r ⎟23 3PR a ⎝ r ⎠=1 S3 = r2 r 13⎛ ++⎞ a3 ⎜⎟⎝ r ⎠ Therefore, the ratio is 1 : 1 Example 19 The 10th common term between the series 3 + 7 + 11 + ... and 1 + 6 + 11 + ... is (A) 191 (B) 193 (C) 211 (D) None of these Solution (A) is the correct answer. The first common term is 11. Now the next common term is obtained by adding L.C.M. of the common difference 4 and 5, i.e., 20. Therefore, 10th common term = T of the AP whose a = 11 and d= 2010T10 = a+ 9 d= 11 + 9 (20) = 191 Example 20 In a G.P. of even number of terms, the sum of all terms is 5 times the sum of the odd terms. The common ratio of the G.P. is −4 1 (A) (B) (C) 4 (D) none the these 55 Solution (C) is the correct answer (2n 2 nar 1) 5(( ) −1− ar )Let us consider a G.P. a, ar, ar2, ... with 2n terms. We have = 2r−1 r −1 (Since common ratio of odd terms will be r2 and number of terms will be n) 2n 2nar( −1) ar( −1) ⇒ = 5 r−1(r2 −1) ⇒ a(r+ 1) = 5a, i.e., r= 4 Example 21 The minimum value of the expression 3x+ 31 – x , x∈ R, is 1 (A)0 (B) (C)3 (D) 3 Solution (D) is the correct answer. We know A.M. ≥ G.M. for positive numbers. x 1− x3 +3 x 1−xTherefore, ≥ 33⋅ 2 x 1− x3 +3 x 3 ⇒ ≥ 3 ⋅ x23 ⇒ 3x+ 31– x ≥ 23 Short Answer Type 1. The first term of an A.P.is a, and the sum of the first pterms is zero, show that ( + )−ap qq the sum of its next qterms is . [Hint: Required sum = Sp+ q– Sp]p−1 2. A man saved Rs 66000 in 20 years. In each succeeding year after the first year he saved Rs 200 more than what he saved in the previous year. How much did he save in the first year? 3. A man accepts a position with an initial salary of Rs 5200 per month. It is understood that he will receive an automatic increase of Rs 320 in the very next month and each month thereafter. (a) Find his salary for the tenth month (b) What is his total earnings during the first year? 4. If the pth and qth terms of a G.P. are qand p respectively, show that its (p+ q)th 1 pq term is ⎜ q⎟ . ⎛ qp⎞− p⎝ ⎠ 5. A carpenter was hired to build 192 window frames. The first day he made five frames and each day, thereafter he made two more frames than he made the day before. How many days did it take him to finish the job? 6. We know the sum of the interior angles of a triangle is 180°. Show that the sums of the interior angles of polygons with 3, 4, 5, 6, ... sides form an arithmetic progression. Find the sum of the interior angles for a 21 sided polygon. 7. A side of an equilateral triangle is 20cm long. A second equilateral triangle is inscribed in it by joining the mid points of the sides of the first triangle. The process is continued as shown in the accompanying diagram. Find the perimeter of the sixth inscribed equilateral triangle. 8. In a potato race 20 potatoes are placed in a line at intervals of 4 metres with the first potato 24 metres from the starting point. A contestant is required to bring the potatoes back to the starting place one at a time. How far would he run in bringing back all the potatoes? 9. In a cricket tournament 16 school teams participated. A sum of Rs 8000 is to be awarded among themselves as prize money. If the last placed team is awarded Rs 275 in prize money and the award increases by the same amount for successive finishing places, how much amount will the first place team receive? 10. If a1, a2, a, ..., a are in A.P., where a > 0 for all i, show that3 n i11 1 n −1+ ++ ... = a1 + a2 a2 + a3 an−1 + an a1 + an 11. Find the sum of the series (33 – 23) + (53 – 43) + (73 – 63) + ... to (i) n terms (ii) 10 terms 12. Find the rth term of an A.P. sum of whose first n terms is 2n + 3n2. [Hint: a = S – S]n nn–1Long Answer Type 13. If A is the arithmetic mean and G1, G2 be two geometric means between any two numbers, then prove that G12 G222A=+ G2 G1 14. If θ, θ, θ, ..., θ are in A.P., whose common difference is d, show that123nn tan θ1tan θ− secθ secθ + secθ secθ + ... + secθ secθ = .1 223n–1n sin d 15. If the sum of p terms of an A.P. is q and the sum of q terms is p, show that the sum of p + q terms is – (p + q). Also, find the sum of first p – q terms (p > q). 16. If pth, qth, and rth terms of an A.P. and G.P. are both a, b and c respectively, show that ab–ca . bc – . ca – b = 1 Objective Type Questions Choose the correct answer out of the four given options in each of the Exercises 17 to 26 (M.C.Q.). 17. If the sum of n terms of an A.P. is given by S n = 3n + 2n2, then the common difference of the A.P. is (A)3 (B)2 (C)6 (D)4 19. 20. 21. 22. 23. 24. 25. 26. SEQUENCE AND SERIES 163 18. The third term of G.P. is 4. The product of its first 5 terms is (A) 43 (B) 44 (C) 45 (D) None of these If 9 times the 9th term of an A.P. is equal to 13 times the 13th term, then the 22nd term of the A.P. is (A) 0 (B) 22 (C) 220 (D) 198 If x, 2y, 3z are in A.P., where the distinct numbers x, y, z are in G.P. then the common ratio of the G.P. is 1 1(A)3 (B) (C)2 (D) 32 If in an A.P., Sn = qn2 and Sm = qm2, where Sr denotes the sum of r terms of the A.P., then Sq equals q3 (A) (B) mnq (C) q3 (D) (m + n) q2 2 Let S n denote the sum of the first n terms of an A.P. If S2n = 3S n then S3 n : S is equal to n(A)4 (B)6 (C)8 (D)10 The minimum value of 4x + 41–x , x ∈ R, is (A)2 (B)4 (C)1 (D)0 Let S denote the sum of the cubes of the first n natural numbers and s denote n nn Srthe sum of the first n natural numbers. Then ∑equalssr=1 r( +1)( n nn( +1) nn +2) (A) (B)6 2 23n2n ++(C) (D) None of these 2 If tn denotes the nth term of the series 2 + 3 + 6 + 11 + 18 + ... then t50 is (A) 492 – 1 (B) 492 (C) 502 + 1 (D) 492 + 2 The lengths of three unequal edges of a rectangular solid block are in G.P. The volume of the block is 216 cm3 and the total surface area is 252cm2. The length of the longest edge is (A) 12 cm (B) 6cm (C) 18 cm (D) 3cm Fill in the blanks in the Exercises 27 to 29. ab− 27. For a, b, c to be in G.P. the value of is equal to .............. .bc− 28. The sum of terms equidistant from the beginning and end in an A.P. is equal to ............ . 29. The third term of a G.P. is 4, the product of the first five terms is ................ . State whether statement in Exercises 30 to 34 are True or False. 30. Two sequences cannot be in both A.P. and G.P. together. 31. Every progression is a sequence but the converse, i.e., every sequence is also a progression need not necessarily be true. 32. Any term of an A.P. (except first) is equal to half the sum of terms which are equidistant from it. 33. The sum or difference of two G.P.s, is again a G.P. 34. If the sum of nterms of a sequence is quadratic expression then it always represents an A.P. Match the questions given under Column I with their appropriate answers given under the Column II. 35. Column I 36. (a) (b) (c) 4, 1, 1 4 , 1 16 2, 3, 5, 7 13, 8, 3, –2, –7 Column I (i) (ii) (iii) (a) 12 + 22 + 32 + ...+n2 (i) (b) 13 + 23 + 33 + ...+n3 (ii) (c) 2 + 4 + 6 + ... + 2n (iii) (d) 1 + 2 + 3 +...+ n (iv) Column II A.P. sequence G.P. Column II ⎛ nn( + 1) ⎞2 ⎜⎟⎝ 2 ⎠ n(n+ 1) ( +1)(2 nnn +1) 6 ( +1) nn2